Éclairage sur les transformations des structures agricoles dans les Alpes - Thomas Streifeneder; Ulrike Tappeiner; Flavio V. Ruffini; Gottfried Tappeiner; Christian Hoffmann (Revue de Géographie Alpine)
The Alpine region registered a substantial abandonment of farms (-40%) between 1980 and 2000. Both Alpine regions with a relatively stable situation (AT, CH) and regions with significant agricultural changes (IT, SI) exist next to each other. The agro-structural change has led to profound changes in operational structures (enlargement of farms, abandonment of utilised agricultural areas, varying shares of socio-economic farm types). This resulted from various cultural (e.g. relatedness to agricultural traditions, identification of the society with agriculture), agro-political (e.g. Common Agricultural Policy/ WTO) and economic (e.g. non-agricultural income possibilities), and operational (e.g. farm-size) driving forces. Next to major national and regional differences within the Alpine Region (e.g. moderate and high farm abandonment), they also face parallels with regard to the change in their agricultural structure (i.e. farm abandonment and increasing farm-size of the remaining farms). Compared to the Alpine-wide average of the changes in the number of farms and the utilised agricultural area (1980-2000), moderate (AT/CH/DE), dynamic (IT/SI), and uncorrelated (FR) were observed.